Performa Finansial Koperasi Serba Usaha Tandangsari Kabupaten Sumedang Sebelum dan Selama Penyakit Kuku dan Mulut - Firman, Achmad; Mauludin, Mochamad Ali; Kusmayadi, Tendy (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
Tandangsari Multipurpose Cooperative (KSU) is the only dairy cooperative in Sumedang Regency. The cooperative is a forum for dairy farmers to distribute their milk production. Along with the outbreak of foot and mouth disease (FMD), milk production has decreased at the farm level. Therefore, the purpose of this study is to analyze milk productivity and cooperative financial performance in 2021 (before FMD) and 2022 (during FMD). The analysis method of this research consists of two, namely the financial performance analysis method using the Regulation of the Deputy for Supervision of the Ministry of Cooperatives and Small and Medium Enterprises (KUKM) of the Republic of Indonesia Number 06/Per/Dep.6/IV/2016 and the key performance index (KPI). The results of this study indicate that the performance of milk production has decreased by 24.75% in 2022 where in that year the FMD outbreak has lasted for eight months.  The financial performance of KSU Tandangsari has a KPI value before and during FMD of 57% and 63%, respectively. Both values are still included in the sufficient category. Even this cooperative was able to improve its KPI during the FMD outbreak.